Analysis of near-fault pulse-like seismic signals through Variational Mode Decomposition technique. (15th August 2019) - Quaranta, Giuseppe; Mollaioli, Fabrizio
Highlights: Pulse-like near-fault earthquakes characterization is addressed. The Variational Decomposition Method is applied to process such seismic records. Pulse period values agree with the estimates obtained using alternative methods. Relevance of modes other than the one that embeds the dominant pulse is analyzed. Abstract: The present work illustrates the results obtained from the application of the Variational Mode Decomposition technique for processing near-fault pulse-like seismic signals. This method has been adopted to analyze a database of fault-normal horizontal impulsive seismic signal components and proved able to extract the mode that embeds the dominant pulse, which is approximated by means of well-known numerical pulse-like waveforms. Pulse period values estimated according to this technique are in good agreement with the ones obtained by means of existing methods. The relevance of modes other than the one that embeds the dominant pulse is finally discussed.